Experimental Study Compressive Strength of Concrete With Palm Shells as a Partial Replacement for Coarse Aggregate - Deded Eka Sahputra; Rita Nasmirayanti; Rafki Imani; Nanang Fatchurrohman; Noto Dewantoro (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
This experimental study aims to evaluate the compressive strength of concrete using palm kernel shells as a substitution for coarse aggregates. The utilization of locally available materials in abundance, such as palm kernel shells, can serve as a sustainable alternative in construction. This research is conducted to measure the influence of palm kernel shell usage on the mechanical properties of concrete, particularly its compressive strength. The research methodology involves the preparation of concrete mixtures with various levels of substitution of coarse aggregates with palm kernel shells. Test specimens were prepared with substitution percentages of 0%, 25%, and 60% with planned ages of 7 days, 21 days, and 28 days. Three cube specimens were cast for each planned age. The test results were used to compare the compressive strength of concrete with and without palm kernel shells and to evaluate the potential of palm kernel shells as a substitute for coarse aggregates in structural concrete applications. The research findings indicate that the highest compressive strength was obtained in the concrete without any palm kernel shell mixture (0%), measuring 379.86 kg/cm2. The highest compressive strength with the substitution of coarse aggregates using palm kernel shells was found in the 25% mixture, with a value of 362.57 kg/cm2, while the lowest percentage was recorded in the 60% mixture, with a value of 270.65 kg/cm2. Palm kernel shells have the potential to be used as a substitute for coarse aggregates in concrete. However, their utilization needs to be carefully analyzed and tailored to the specific conditions and requirements of construction projects. This research provides initial insights into the use of palm kernel shells in concrete and can serve as a foundation for further research in the development of environmentally friendly concrete using sustainable local raw materials